ANALYSIS OF SMARTPHONE POLICY AS A LEARNING MEDIA ON COMMUNITY HEALTH STUDY PROGRAM IN STIKES NAULI HUSADA SIBOLGA: ANALISIS KEBIJAKAN SMARTPHONE SEBAGAI MEDIA PEMBELAJARAN PADA PROGRAM STUDI KESEHATAN MASYARAKAT DI STIKES NAULI HUSADA SIBOLGA - Yati Simatupang, Mei (LPPM UPMI, 2023)
Educational policy is a policy in the field of education, to achieve the nation's development goals in the education sector, as one of the goals of our nation. Education policy must be in line with public policy. Technological advances and the widespread development of global information infrastructure have changed the pattern of activities of human life, especially students in the field of health education as smartphone users that allow students to easily access information. The purpose of this study was to analyze whether smartphones can be accepted as a learning media and the impact of smartphone use on students. The research methodology used is the mixed method with a qualitative descriptive approach, in May 2020, with a sample of 50 people. Data collected through questionnaires concluded that: (1) The application of learning media through the use of smartphones in the learning process is a lecturer's innovation in the learning process according to the appropriate consideration of learning media (2) The application of learning media has a positive effect on students' understanding ability in learning. This can be indicated because they have broader knowledge, furthermore they are critical, it can be seen when they dare to express their arguments. The recommended policy is to take a family approach, because the family is a very important part in monitoring the use of smartphones, doing prevention by counseling about the benefits of using smartphones, doing positive activities such as student self-development, implementing regulations for using smartphones on campus and at home.